2017
DOI: 10.1371/journal.pone.0169622
|View full text |Cite
|
Sign up to set email alerts
|

NF-kappaB Is Involved in the Regulation of EMT Genes in Breast Cancer Cells

Abstract: The metastatic process in breast cancer is related to the expression of the epithelial-to-mesenchymal transition transcription factors (EMT-TFs) SNAIL, SLUG, SIP1 and TWIST1. EMT-TFs and nuclear factor-κB (NF-κB) activation have been associated with aggressiveness and metastatic potential in carcinomas. Here, we sought to examine the role of NF-κB in the aggressive properties and regulation of EMT-TFs in human breast cancer cells. Blocking NF-κB/p65 activity by reducing its transcript and protein levels (throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
205
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(212 citation statements)
references
References 57 publications
3
205
0
4
Order By: Relevance
“…However, the recent two separate studies simultaneously did not find the direct and causal evidence, suggesting that there seems to be no causal relationship between EMT and metastasis of cancer. Furthermore, we also presented that IL‐1β was able to activate the NF‐κB signaling pathway, thereby may account for the underlying working mechanism behind M2 macrophages promoted migration and invasion of ESCC cells in view of the activated NF‐κB signaling pathway was shown to be involved in EMT process …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the recent two separate studies simultaneously did not find the direct and causal evidence, suggesting that there seems to be no causal relationship between EMT and metastasis of cancer. Furthermore, we also presented that IL‐1β was able to activate the NF‐κB signaling pathway, thereby may account for the underlying working mechanism behind M2 macrophages promoted migration and invasion of ESCC cells in view of the activated NF‐κB signaling pathway was shown to be involved in EMT process …”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, we also presented that IL-1β was able to activate the NF-κB signaling pathway, thereby may account for the underlying working mechanism behind M2 macrophages promoted migration and invasion of ESCC cells in view of the activated NF-κB signaling pathway was shown to be involved in EMT process. 26,27 Despite here we presented some data regarding the involvement of M2 macrophages in the promoting of metastasis of ESCC cells, thereby providing a possible explanation for its potential working mechanism in ESCC; there have been still some limitations that deserve to be noted in that, first, considering the specificity of CD163 for M2 macrophages and that M2 macrophages have other wellaccepted specific surface markers as well, including CD206 28,29 and CD204, 9,28 other than CD163 we selected and used in our current study; only detection of CD163 expression that was made to stand for the infiltrated M2 macrophages should have been strengthened with double staining of other specific surface markers of M2 macrophages meanwhile except of CD163; Second, Interpretation of our results should be approached with caution in that, we selected the IL-1β as cytokine of interest among the six identified and screened out significantly differential protein factors released from M2 macrophages did not mean that only IL-1β played the promoting role in the metastasis of ESCC cells but just showed that IL-1β from M2 macrophages can promote migration and invasion of ESCC cells inducing EMT and activating the NF-κB signaling pathway; Third, theoretical targetability of IL-1β in ESCC obviously needs to be further investigated and evaluated both in vitro and in vivo using animal model experiment.…”
Section: Discussionmentioning
confidence: 99%
“…3B). Inflammation was recognized as an important trigger of EMT [13]. NF-κB signaling is closely related with inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…NF‐κB‐induced gene expression is also responsible for cancer cell migration and invasion. Numerous NF‐κB targets such as TWIST1, SLUG ( SNAIL2 ) ,SIP1 (ZEB2), and MMPs promote EMT in breast BrCa . Numerous reports have reported that upregulated expression of E‐cadherin, the most important marker of epithelial cells, is a result of inhibiting NF‐κB activation, which was associated with reducing transcriptional repressors of E‐cadherin in multiple cancer types .…”
Section: Discussionmentioning
confidence: 99%
“…19,20 NF-κB translocation into nuclei and promotion of gene transcription in BrCa is also a common phenomenon, which is believed to enhance tumor cell survival, proliferation, invasion, and EMT. 21,22 In general, NF-κB is thought to be a cell survival factor because it contributes to cell survival and proliferation. 23 Several NF-κB targets such as cIAP-1, cIAP-2, TRAF1, TRAF2, and Bcl-xL have antiapoptotic properties.…”
Section: Discussionmentioning
confidence: 99%